The efficacy and safety of tenofovir alafenamide versus tenofovir disoproxil fumarate in antiretroviral regimens for HIV-1 therapy: Meta-analysis. Issue 41 (October 2016) - Wang, Huilian; Lu, Xi; Yang, Xudong; Xu, Nan
Abstract: Background: To date, a definite conclusion about efficiency and safety of tenofovir alafenamide for patients with HIV-1 is not available. The aim of the study was to investigate the efficacy and safety of TAF versus TDF in antiretroviral regimens for patients with HIV-1. Methods: PUBMED, MEDLINE, and EMBASE database were searched in March 2016, with no language restriction, for randomized controlled trials (RCTs). Results: Six RCTs (n = 5888) met entry criteria. At week 48, viral suppression rates were similar between TAF and TDF group (90.2% vs 89.5%) for the naive patients. Interestingly, the rate was higher in patients who switched to TAF regimens compared with patients who continued previous TDF regimens (96.4% vs 93.1%). Both groups were generally well tolerated with high barrier to resistance. As compared to TDF, TAF had significantly smaller reductions in eGFR-CG, smaller changes in RBP/Cr and urineβ-2 M/Cr ratio, and less reduction in spine and hip BMD for the treatment-naive patients. Moreover, the switched group had significant efficacy advantages of improving renal function and BMD, including significant decreases in urine albumin/Cr, urine protein/Cr, urine RBP/Cr, and urine β-2 M/Cr ratios, and increases in hip and spine BMD by 1.47% and 1.56%, respectively, as compared with continued TDF regimens. Conclusions: TAF has a similar tolerability, safety, and effectiveness to TDF and probably less adverse events related to renal and bone density outcomes in the treatment of naive and experienced patients with HIV-1. Abstract : Supplemental Digital Content is available in the text